Increased Number of Megakaryocytes in the Synovium and Cartilage of Arthritic Mouse Joints - Petya, Ganova; Nina, Ivanovska (International Journal of Inflammation Research, 2018)
Bone remodeling processes in rheumatoid arthritis (RA) depend mainly on the action of three types of cells. Osteoblasts are responsible for the formation of new bone, osteoclasts degrade mineralized bone and osteocytes regulate and maintain the bone homeostasis. Except, many other cell populations become pathologically activated in the inflamed microenvironment of the joint. The role of megakaryocytes and platelets in RA is poorly clarified. In the present study the presence of MK in the synovium and cartilage was observed in a model of arthritis induced in normal and complement depleted mice.
Keywords: megakaryocytes; complement; P-selectin; zymosan-induced arthritis; platelets; cobra venom factor